(untitled) (Journal of the College of Basic Education, 2023)
The study deals with the issue of referral under the name of "Conscientious Referral in the Poetry of Salman Dawood Muhammad". Through the study, it is clear that the phenomenon of referral does not address the structural level alone, but rather transcends the limits of composition after moving from the limits of a single sentence (i.e. the analysis of sentence elements) to the study of larger text units, concerned with a successive series. sentences, and this care led to monitoring new relationships and tools for understanding the text, in a way that achieves cohesion of its parts,